Modernisasi Tanpa Pembangunan Dalam Proyek Food Estate Di Bulungan Dan Merauke - Kamin, Anggalih Bayu Muh.; Altamaha, Reza (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: Transmigration has been related to efforts to boost food productivity. During the New Order era, transmigration was promoted in order to create cheap labor on large government-owned plantations. After the New Order period, transmigration was once again made to support food program initiated through food estate project. This study wants to explore the paradox of the process of modernization of large-scale agriculture through a food estate project which turned out causing negative impacts for transmigrant farmers and local residents. This research is a literature study carried out by searching research reports, government documents, journal articles, and news from various media concerning the implementation of food estate. Data analysis was carried out through several stages, namely data reduction, data presentation, verification and conclusion drawing. This study has discovered how the large-scale agricultural modernization projects in Merauke and Bulungan is not an effort to support food security, but merely a broad-scale agribusiness expansion. The implementation of transmigration, basically, only serves as a support to ease the agribusiness expansion that takes place in Merauke and Bulungan. This study has proven the condition of food insecurity that must be faced by transmigrant farmers & local residents affected by the project. Intisari: Transmigrasi selama ini terkait dengan upaya menggenjot produktivitas pangan. Pada masa Orde Baru, transmigrasi digalakkan dengan untuk menjadikan transmigran sebagai tenaga kerja murah di perkebunan besar milik pemerintah. Setelah masa Orde Baru berakhir, transmigrasi dijadikan lagi sebagai penopang program pangan dengan dicetuskannya proyek food estate. Kajian ini ingin mendalami paradoks dari proses modernisasi pertanian skala luas melalui proyek food estate yang justru menyebabkan dampak negatif bagi petani transmigran dan penduduk lokal. Penelitian ini merupakan studi literatur yang dilakukan dengan melakukan penelusuran terhadap laporan penelitian, dokumen pemerintahan, artikel jurnal, dan berita dari berbagai media yang terkait dengan pelaksanaan food estate. Analisis data dilakukan melalui beberapa tahapan, yakni reduksi data, penyajian data, verifikasi dan penarikan kesimpulan. Kajian ini telah menemukan bagaimana proyek modernisasi pertanian dalam skala luas di Merauke dan Bulungan bukanlah usaha menjaga ketahanan pangan, melainkan semata ekspansi agribisnis dalam skala luas. Penyelenggaraan transmigrasi pada dasarnya hanya menjadi penopang untuk memfasilitasi ekspansi agribisnis yang terjadi di Merauke dan Bulungan. Kajian ini telah membuktikan kondisi kerawanan pangan yang harus dihadapi petani transmigran & penduduk lokal terdampak proyek.